Bentuk Pelaksanaan Demokrasi Pertama di Indonesia - Teguh Dias Arestu (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2021)
liberal democracy begins When indenesia has held a session in the KMB to form a parliamentary. As the cabinet progresses, the policy pattern depends on the prime minister who is in charge of his time. Like the burhanudin harahap cabinet which made the first election work program in Indonesia, which threw many countries around